Design and Realization of 3D-Kriging System Based on .NET - Yuqin Yuan; Xianchuan Yu; Junlan Zhang; Huandong Chen; Shulei Wu (2009 Second International Conference on Intelligent Networks and Intelligent Systems, 2009)
The paper proposes a new 3D-kriging system based on Microsoft Visual Studio.NET 2003. The system was module designed and has high quality of 3D visualization and friendly user interface by using some 3D dynamic display such as OpenGL. Compared with other popular geostatistical softwares, the system has its own advantages.